Advances in laparoscopic surgery in urology - Rassweiler, Jens J.; Teber, Dogu (Nature reviews. Urology, 2016)
Key Points Robot-assisted surgery has revolutionized laparoscopy, particularly enabling surgeons with no laparoscopic training to learn and perform reconstructive procedures with a shortened learning curve Laparoscopic surgery will benefit from new developments, such as 4K ultrahigh-definition and 3D high-definition video technology, flexible instruments, suturing devices, and sealing devices using bipolar and ultrasound technology Sophisticated camera holders and ergonomic platforms, enabling the surgeon to perform the procedure in a sitting position or with arm and chest support, will further benefit laparoscopic surgery The use of specific platforms for single-site surgery might increase the application of laparoendoscopic single-site surgery for urological indications Laparoscopy remains an important surgical technique, particularly for ablative procedures Distribution of robot-assisted surgery is limited by high purchase and maintenance costs for the only existing robotic system, but new robots are expected soon Laparoscopic techniques are subject to continuous change and benefit from new developments. Robot-assisted surgery has substantially revolutionized laparoscopy, increasing its distribution; however, it is associated with considerable costs. In this Review, Rassweiler and Teber discuss technical improvements, developing technologies and speculate on the future of minimally invasive surgery and laparoscopy in urology. In the past 10 years, laparoscopy has been challenged by robotic surgery; nevertheless, laparoscopic techniques are subject to continuous change. Ultrahigh definition is the next development in video technology, it delivers fourfold more detail than full high definition resulting in improved fine detail, increased texture, and an almost photographic emulsion of smoothness of the image. New 4K ultrahigh-definition technology might remove the current need for the use of polarized glasses. New devices for laparoscopy include advanced sealing devices, instruments with six degrees of freedom, ergonomic platforms with armrests and a chest support, and camera holders. A manually manipulated robot-like device is still at the experimental stage. Robot-assisted surgery has substantially revolutionized laparoscopy, increasing its distribution; however, robot-assisted surgery is associated with considerable costs. All technical improvements of laparoscopic surgery are extremely valuable to further simplify the use of classical laparoscopy.